PTU-032 Post-colonoscopy colorectal cancer rates in IBD are high and vary by NHS trust in england. (8th June 2018) - Burr, Nicholas; Valori, Roland; Subramanian, Venkataraman; Hull, Mark; Shelton, Jon; Pearson, Clare; Smith, Andy; Morris, Eva; Rutter, Matthew
Abstract : Introduction: Colorectal cancer (CRC) risk is increased in those with inflammatory bowel disease (IBD). Guidelines advocate surveillance colonoscopy for patients with longstanding IBD. Post-colonoscopy colorectal cancer (PCCRC) is a key quality indicator of colonoscopy. There is limited data exploring the rate of PCCRC in those with IBD and potential risk factors associated with IBD-related PCCRC. This study explored national and individual hospital rates of IBD-related PCCRC in England since 2006. Further analysis explored potential associations with IBD-related PCCRC in order to inform future quality improvement interventions. Methods: We identified all those who had undergone a colonoscopy between 1/1/2006 and 31/12/2012 and developed a CRC before 31/12/2015 using linked national Hospital Episode Statistics and National Cancer Registration and Analysis Service data. IBD cases were identified by relevant ICD-10 codes. Using international consensus guidelines 1, 2 the rate of PCCRC within 3 years (PCCRC-3 yr) was calculated as the number of false negative colonoscopies (within 6–36 months of CRC) divided by the sum of the true positive (within 6 months of CRC) and false negative colonoscopies. The IBD-associated PCCRC-3 yr rate in each NHS hospital trust in England was ranked and trusts were separated into quintiles. Factors associated with IBD-related PCCRC were investigated. Results: Between 2006 and 2012 we identified 7781 PCCRC, 800 (10%) with a diagnosis of IBD. Nationally, the IBD-PCCRC-3 yr rate was 35%, and varied between hospital trusts with those in the lowest quintile having a mean, unadjusted rate of 19% (SD ±7%) compared to 52% (SD ±7%) in the highest quintile. PCCRC cases were younger at diagnosis (60 years compared to 66 years), were less likely to have diverticular disease (10% compared to 16%), and had undergone more previous colonoscopies when compared to detected cases (within 6 months of colonoscopy). There was no significant difference for sex, bowel location, deprivation score, or metachronous tumours. Conclusion: PCCRC-3 yr in those with IBD is high, and accounted for 10% of all PCCRC-3 yr in England between 2006 and 2012. There is a wide variation in the unadjusted rates between NHS trusts in England that is unlikely to be explained by natural variation. There is an urgent need to investigate avoidable reasons for cancers in those with IBD to optimise surveillance and prevention of CRC in IBD.